2018
DOI: 10.1007/s00216-018-1143-2
|View full text |Cite
|
Sign up to set email alerts
|

A colorimetric assay of DNA methyltransferase activity based on peroxidase mimicking of DNA template Ag/Pt bimetallic nanoclusters

Abstract: DNA methylation catalyzed by DNA methyl transferase (MTase) is a significant epigenetic process for modulating gene expression. Abnormal levels of DNA MTase enzyme have been regarded as a cancer biomarker or a sign of bacterial diseases. We developed a novel colorimetric method to assay M.SssI MTase activity employing peroxidase-like activity of DNA template Ag/Pt NCs without using restriction enzymes. Based on inhibiting the peroxidase reaction that occurred in the TMB-HO system, in the presence of MTase, a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…In addition, the MSP assay only provides qualitative results instead of quantitative data due to the visual readout of detection results via agarose gel electrophoresis. In recent years, a variety of PCR-free strategies have been developed for the sensitive quantification of DNA methylation, such as fluorescence assay, 12,13 electrochemical enzymatic assay, 14 colorimetry, [15][16][17] and Raman spectroscopy. 18,19 Shiddiky et al reported a global DNA methylation screening method in a PCR-free way by utilizing electrochemical enzymatic signal engagement.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the MSP assay only provides qualitative results instead of quantitative data due to the visual readout of detection results via agarose gel electrophoresis. In recent years, a variety of PCR-free strategies have been developed for the sensitive quantification of DNA methylation, such as fluorescence assay, 12,13 electrochemical enzymatic assay, 14 colorimetry, [15][16][17] and Raman spectroscopy. 18,19 Shiddiky et al reported a global DNA methylation screening method in a PCR-free way by utilizing electrochemical enzymatic signal engagement.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with natural enzymes, nanozymes have higher stability and multifunctionality leading to their numerous application. [1][2][3][4][5][6] Nanozymes have also been used in biosensors to detect different molecules, cancer cells, and other targets. [7][8][9][10][11][12][13] To date, an extensive range of nanozymes with enzymatic properties for detection of glucose has been reported; for instance, Au NPs, Ag NPs, Pt NPs and their alloys, [14] carbon-based nanomaterials, [15][16][17] metal-organic frameworks (MOFs), [18] Tungsten disulfide (WS 2 ) nanosheets, [15] etc.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these nanomaterials have been studied extensively and yielded acceptable results. Compared with natural enzymes, nanozymes have higher stability and multifunctionality leading to their numerous application [1–6] . Nanozymes have also been used in biosensors to detect different molecules, cancer cells, and other targets [7–13] .…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] The conventional methods for the detection of MTase enzyme activity and methylated DNA include bisulte treatment, 11 high performance liquid chromatography (HPLC), 12 electrochemistry, [13][14][15][16][17] enzyme-linked immunosorbent assay (ELISA), 18 surface plasmon resonance (SPR) spectroscopy, 19,20 surface-enhanced Raman scattering (SERS), 21,22 and use of microuidic based biosensors 23,24 and uorescence based biosensors. [25][26][27][28] Although several attempts have been made for the detection of methylated DNA in recent years, there are still some drawbacks that limit their sensitivity and efficacy in clinical applications.…”
Section: Introductionmentioning
confidence: 99%